166k views
1 vote
Simplify the algebraic expression. (m - 7) + 5(m - 3)

User Wkhatch
by
4.6k points

2 Answers

3 votes

Answer: 6m-22

Explanation:

Given

(m-7)+5(m-3)

Take off parentheses/distributive property

= m-7+5m-15

Move like terms together

=m+5m-7-15

Combine like term

=6m-22

Hope this helps!! :)

Please let me know if you have any question

User GilZ
by
4.7k points
3 votes

Answer:

6m -22

Explanation:

(m - 7) + 5(m - 3)

= m - 7 + 5m - 15

= 6m -22

User Pinewood
by
4.5k points